Pengaruh Persepsi Masyarakat Lokal Terhadap Pengembangan Kampung Wisata - Huang, Kimberly; Dewanta Facrureza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to determine the influence of local community perceptions on the development of the Tourism Village. This research method used a quantitative approach, with questionnaires distributed to 100 respondents living in the Kampung Silat Rawa Belong Tourism Village area as the research sample. Data analysis was conducted using SPSS. The results showed that local community perceptions, both cognitive, affective, and conative, had a positive and significant influence on the development of the Kampung Silat Rawa Belong Tourism Village. These three dimensions simultaneously explained 33.2% of the contribution to the development of the Tourism Village, while the remainder was influenced by external factors such as infrastructure and government policies. This study concluded that all dimensions of community perception—cognitive, affective, and conative—had a positive and significant influence, both partially and simultaneously, on the development of the Kampung Silat Rawa Belong Tourism Village. Keywords: Community Perception, Tourism Village, Tourism Village Development.